Cytosolic GDH1 degradation restricts protein synthesis to sustain tumor cell survival following amino acid deprivation. (16th July 2021) - Shao, Jialiang; Shi, Tiezhu; Yu, Hua; Ding, Yufeng; Li, Liping; Wang, Xiang; Wang, Xiongjun
Abstract: The mTORC1 pathway plays key roles in regulating various biological processes, including sensing amino acid deprivation and driving expression of ribosomal protein (RP)‐coding genes. In this study, we observed that depletion of glutamate dehydrogenase 1 (GDH1), an enzyme that converts glutamate to α‐ketoglutarate (αKG), confers resistance to amino acid deprivation on kidney renal clear cell carcinoma (KIRC) cells. Mechanistically, under conditions of adequate nutrition, GDH1 maintains RP gene expression in a manner dependent on its enzymatic activity. Following amino acid deprivation or mTORC1 inhibition, GDH1 translocates from mitochondria to the cytoplasm, where it becomes ubiquitinated and degraded via the E3 ligase RNF213. GDH1 degradation reduces intracellular αKG levels by more than half and decreases the activity of αKG‐dependent lysine demethylases (KDMs). Reduced KDM activity in turn leads to increased histone H3 lysine 9 and 27 methylation, further suppressing RP gene expression and preserving nutrition to support cell survival. In summary, our study exemplifies an economical and efficient strategy of solid tumor cells for coping with amino acid deficiency, which might in the future be targeted to block renal carcinoma progression. SYNOPSIS: Tumor cells need to cope with nutritional exhaustion during cancer progression. A mechanism downregulating glutamate dehydrogenase 1 (GDH1) and ribosomal protein expression upon amino acid deprivation exemplifies an economical and efficient strategy employed by KIRC solid tumor cells. GDH1 depletion confers tolerance to amino acid deprivation on kidney renal clear cell carcinoma (KIRC) cells. Amino acid deprivation or mTORC1 inhibition induces GDH1 translocation from mitochondria to the cytoplasm. Cytoplasmic GDH1 is ubiquitinated by the RNF213 E3 ligase and degraded. GDH1 degradation reduces intracellular α‐ketoglutarate levels and activity of lysine demethylases such as KDM4A and KDM6A. Increased histone methylation after KDM reduction suppresses ribosomal protein expression. Abstract : RNF123‐mediated degradation of glutamate dehydrogenase 1 reduces α‐ketoglutarate‐dependent lysine demethylase activity, which leads to a decrease in ribosomal protein expression under low‐nutrient conditions.